Pengembangan SDM Pesantren melalui Komunikasi Kelompok di Pondok Pesantren Darul Hikmah Narathiwat Thailand - FASADENA, NOVA; Nur Hamida; Iezzatun Hasanah; Bunga Surawijaya Ningsih; Kartika Bina Kasih (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2025)
This research addresses the issue of human resource development at Pondok Pesantren Darul Hikmah, Narathiwat, Thailand, focusing on enhancing students' social and leadership skills through group communication. The aim of this research is to develop students' social skills, leadership, and critical thinking, while creating an inclusive and supportive learning environment. The implementation method used Asset-Based Community Development which conclude inculturate, discovery, dream, design, define, and destiny. The results of the empowerment show that students became more active in discussions, improved their critical thinking skills, and developed leadership abilities. Additionally, group communication successfully created a more harmonious learning environment and strengthened solidarity among students. Therefore, this approach has proven to be effective in improving education quality and character development in the pesantren.